CRPP for Extension Type III Supracondylar Fracture of Humerus by Lateral versus Crossed K Wires – a Comparative Hospital Based Study - K C, Samir; Sharma Kandel, Ishwar; Shrestha, Bhola; Bista, Krishna Bahadur; Dhakal, Rabi Mohan; Parajuli, Pravakar; Shrestha, Debesh; Duwal Shrestha, Sailendra Kumar; Nepal, Prabin; Karki, Netra Bahadur (Journal of Karnali Academy of Health Sciences, 2022)
Background: SCFH accounts for sixty percent of all fractures around elbow. Type III SCFH is unstable. CRPP is treatment of choice. Both the crossed-k wires and lateral-entry k wires have been used successfully; however, superiority has not been established. This study compares stability, functional outcomes, radiological outcomes and complications of these two methods. Methods: This is a hospital based prospective comparative study undertaken at GMCTH from June 2019 to November 2020. Fifty-six children of three to thirteen years with extension type III SCFH were included after taking informed consent. Ethical clearance was taken from NHRC, Kathmandu. Patients were followed up for three months. Statistical analysis was done using SPSS 25 and p value <0.05 was considered significant. Results: The average age of participants was 7.70 years. There were 15 girls (26.7%) and 41 boys (73.3%). Right sided injuries occurred in 32.1% of children with 78.6% sustaining injury on the non-dominant side. Mean duration of fracture healing was 4.75 weeks. Average Baumann’s angle at three completed months in lateral-entry group was 75.04 degrees and crossed-K wires was 74.50 degrees (p=0.374). The average carrying angle in lateral-entry group was 7.79 and crossed-K wires was 7.29 degrees (p=0.303). Average loss of flexion in lateral-entry group was 2.71 degrees and 2.25 degrees in crossed-K wires (p=0.479). Average loss of extension in lateral-entry group was 3.39 degrees and crossed-K wires was 2.82 degrees (p=0.37). Skaggs et al Criteria for grading loss of reduction showed no loss of reduction in all fifty-six cases. Conclusion: Both the lateral and cross pinning techniques are equally efficient in maintaining reduction in management of supracondylar fracture of humerus. The ulnar nerve injury can be avoided while using the medial K wire by pinning in a semi-flexed elbow with ulnar nerve rolled back.